Organic Reactions 1988
DOI: 10.1002/0471264180.or035.01
|View full text |Cite
|
Sign up to set email alerts
|

TheBeckmann Reactions: Rearrangements, Elimination–Additions, Fragmentations, and Rearrangement–Cyclizations

Abstract: The Beckmann rearrangement, the acid‐mediated isomerization of oximes to amides, was discovered by Beckmann in 1886. As one of the oldest and most familiar transformations in organic chemistry, it has been reviewed several times. What has become known as the Beckmann fragmentation was in fact first observed by Wallach in 1889 but was not developed extensively until the 1960s. It has been referred to by several names over the years and has also been reviewed. The rearrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 396 publications
2
60
0
1
Order By: Relevance
“…However, a very few apparent exceptions have been documented under certain reaction conditions (8,13). If a syn-migration product is formed, it has been assumed that isomerization of the oxime occurs before rearrangement (6)(7)(8)13). However, such isomerization of the oximes does not occur in the present case.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…However, a very few apparent exceptions have been documented under certain reaction conditions (8,13). If a syn-migration product is formed, it has been assumed that isomerization of the oxime occurs before rearrangement (6)(7)(8)13). However, such isomerization of the oximes does not occur in the present case.…”
mentioning
confidence: 72%
“…It is generally accepted that the Beckmann rearrangement of ketoximes is stereospecific, that N-O bond cleavage occurs with simultaneous migration (e.g., in the cases of O-tosyl (Ts)-phenyl-2-propanone oxime derivatives) (10)(11)(12), and that the relevant C-C bond anti to the leaving group on nitrogen atom migrates (i.e., anti-migration) occurs to maximize antiperiplanar electron delocalization of the C-C σ orbital to the antibonding σ* orbital of the N-O bond (Fig. 2B) (6,7,(10)(11)(12). However, a very few apparent exceptions have been documented under certain reaction conditions (8,13).…”
mentioning
confidence: 99%
“…128,129 The Beckmann rearrangement generally requires a very high reaction temperature and strong acidic conditions. However, Gai and coworkers have recently revealed that conversion of various ketoximes efficiently takes place under a moderate-temperature regime (130 • C) in the presence of tungstated zirconia solid acid nanocatalysts (5-35 wt% of W).…”
Section: Other Rearrangementsmentioning
confidence: 99%
“…Beckmann rearrangement, discovered 130 years ago, has been widely used for the purposes of modern organic synthesis of large variety of natural products, pharmaceuticals and products of bulk industrial processes [1][2][3].…”
Section: Introductionmentioning
confidence: 99%